Comparison of tympanic membrane injuries between hanging and other non-asphyxiating deaths by otoscopic examination - Kosalakood, Pesoln; Meesilpavikkai, Koravik; Isipradit, Permsarp (Chulalongkorn Medical Journal, 2023)
Background : Hanging is the most frequent suicidal method. It can cause tympanic membrane (TM) injuries. Otoscopic examination is a non-invasive procedure to explore TM injuries that may be related to the pathological changes from hanging. Objective : To evaluate the value of TM injuries as a diagnostic tool in hanging cases. Methods : We prospectively examined 20 of hanging cases and 12 of non-asphyxiating deaths by otoscopic examination, photographed and blindly evaluated TM injuries by an otolaryngologist from grade 0 to grade 3 according to severity. P – value, confidence of interval, sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), area under the curve, and odd ratio (OR) were used to explore the correlation between TM injuries and hanging. Results : There was higher number of TM injuries in the hanging cases than nonasphyxiating cases. (OR = 5.293 at 95% CI, 1.290 – 21.72413 with P - value = 0.0149 for right ear and OR = 3.579 at 95% CI, 1.354 – 12.645, P - value = 0.0091 for left ear. Diagnostic odds ratio = 8.748) Conclusions : The injuries found in ears tympanic membrane seemed to be the indicative findings in hanging. A larger sample size will be required to yield more accurate study results.